The emerging role of exosomes in innate immunity, diagnosis and therapy - Gangadaran, Prakash; Madhyastha, Harishkumar; Madhyastha, Radha; Rajendran, Ramya Lakshmi; Nakajima, Yuichi; Watanabe, Nozomi; Velikkakath, Anoop Kumar G.; Hong, Chae Moon; Gopi, Rahul Velikkakath; Muthukalianan, Gothandam Kodiveri; Valsala Gopalakrishnan, Abilash; Jeyaraman, Madhan; et al. (Frontiers in Immunology, 2023)
Exosomes, which are nano-sized transport bio-vehicles, play a pivotal role in maintaining homeostasis by exchanging genetic or metabolic information between different cells. Exosomes can also play a vital role in transferring virulent factors between the host and parasite, thereby regulating host gene expression and the immune interphase. The association of inflammation with disease development and the potential of exosomes to enhance or mitigate inflammatory pathways support the notion that exosomes have the potential to alter the course of a disease. Clinical trials exploring the role of exosomes in cancer, osteoporosis, and renal, neurological, and pulmonary disorders are currently underway. Notably, the information available on the signatory efficacy of exosomes in immune-related disorders remains elusive and sporadic. In this review, we discuss immune cell-derived exosomes and their application in immunotherapy, including those against autoimmune connective tissue diseases. Further, we have elucidated our views on the major issues in immune-related pathophysiological processes. Therefore, the information presented in this review highlights the role of exosomes as promising strategies and clinical tools for immune regulation.